Pengaruh Gaji, Fasilitas, dan Motivasi Kerja Terhadap Kinerja Karyawan : Studi Kasus Shopee Xpress DC Surabaya - Muzabir Muhammad; Salman Alfarisi; Rifqi Dhiyaul Rahman; Nindya Kartika Kusmayati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine how salary, facilities and work motivation affect employee performance. . Shopee Xpress Distribution Center (DC) Surabaya. This study adopts a survey approach through quantitative methods. A total of 57 respondents were selected using a purposive sampling technique with certain criteria. The research tool being used is a closed questionnaire with a Likert scale and consists of 57 statements, covering four main variables: salary, facilities, work motivation and employee performance. Information obtained from the analysis using multiple linear regression. The study findings show that simultaneously, salary, facilities, and work motivation have a significant influence on employee performance. But partially, only salary shows a significant influence on performance, while facilities and work motivation do not have a significant influence. The coefficient of determination R² of 0.219 indicates that the three independent variables explain 21.9% of the variability in employee performance, while other factors outside this study affect the rest. This finding emphasizes that good compensation system management is very important to improve employee performance. in a logistics organization like Shopee Xpress